Microstructural evolution of pure silver during ECAP processing and subsequent heating. (1st January 2013) - Bassani, Paola; Biffi, Carlo Alberto; Tuissi, Ausonio; Angella, Giuliano; Casati, Riccardo; Vedani, Maurizio
In recent years large research efforts have been focused on the development of severe plastic deformation (SPD) processes to produce ultrafine grained metals. One of the most studied methods for SPD processing is equal channel angular pressing, widely applied to different metals. Silver is one of the material recently subjected to this type of deformation process, since it is a representative FCC metal with low stacking fault energy (SFE). Limited information exists on structure evolution and deformation mechanisms of silver and its alloys in the ultrafine and nanoscale grain size range, and on thermal stability of these microstructures. In particular, low temperature, or even room-temperature, self-annealing is a fundamental issue to be faced for industrial applications. An evaluation of microstructure stability through X-ray diffraction measurements during step-heating treatments is proposed here, instead of multiple isothermal treatments. The method allowed to confirm that restoration temperature decreases for increasing deformation, and it achieves a saturation value after four ECAP passes.